Post-Flood Recovery and Disaster-Resilient Education Policy Implementation in Islamic Schools in Aceh Tamiang - Muhammad Jailani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examined the impact of the 2025–2026 flood disaster on Islamic educational institutions in Aceh Tamiang Regency, Indonesia, and analyzed the local implementation gap of the Disaster-Safe Education Unit (Satuan Pendidikan Aman Bencana [SPAB]) policy. Using a qualitative Participatory Action Research (PAR) approach, data were collected through in-depth interviews with 25 key informants (school principals, teachers, students, education officials, and disaster-management officers), repeated field observations, and document analysis. Three main findings emerged. First, the floods caused severe damage to educational infrastructure, affected 394 educational facilities, interrupted learning for almost one month, and generated psychosocial distress among students and educators. Second, although a national SPAB framework was available, local implementation was constrained by weak inter-agency coordination, limited regulatory support, uneven aid distribution, and insufficient preparedness capacity. Third, community solidarity and teacher-led initiatives grounded in Islamic values—particularly ta‘āwun (mutual assistance) and amanah (responsibility)—helped sustain educational continuity through temporary learning spaces, class rotation, and community support. From a maqāṣid al-sharī‘ah perspective, protecting learning continuity supported the protection of life (ḥifẓ al-nafs) and intellect (ḥifẓ al-‘aql). The study proposes a 2026–2030 regional recovery roadmap integrating flood-responsive infrastructure, institutionalized SPAB governance, psychosocial recovery, and Islamic ethical-value internalization. The study is limited by its single-region focus, reliance on self-reported accounts, and the absence of a standardized count of observation sessions. The findings contribute an integrative model of disaster-resilient Islamic education that combines technical mitigation with faith-based community resilience